2005
DOI: 10.1016/j.orthres.2004.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin‐1 is secreted after total knee arthroplasty regardless of the use of a tourniquet

Abstract: Early infections and wound healing disorders after implantation of a total knee replacement occur regardless of the intraoperative use of a tourniquet. The biochemical regulatory processes responsible for the disturbances in microcirculation and thus the potential therapeutic options have yet to be elucidated. The hypothesis of the present paper was that endothelin-1 (ET-l), a mediator of microcirculation disturbances in parenchymatous organs, also is released after major operations on peripheral joints.The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…Several randomized controlled trials of tourniquet versus no tourniquet use during this operation have shown no statistical difference or even less total blood loss when no tourniquet is used [1,2,10,12,14,15,[25][26][27][28][29] . Moreover, there are potential complications associated with tourniquet use: nerve palsy [8,19], delayed recovery of muscle power from microscopic changes in muscle myofibrils [21], wound complications [1,12,25], and venous thrombotic embolism [1,10,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several randomized controlled trials of tourniquet versus no tourniquet use during this operation have shown no statistical difference or even less total blood loss when no tourniquet is used [1,2,10,12,14,15,[25][26][27][28][29] . Moreover, there are potential complications associated with tourniquet use: nerve palsy [8,19], delayed recovery of muscle power from microscopic changes in muscle myofibrils [21], wound complications [1,12,25], and venous thrombotic embolism [1,10,12].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there are no studies in the literature comparing the use of the tourniquet during cementation only with tourniquet use during the entire operation. All previous randomized studies have compared no tourniquet use at all with tourniquet use during the operation [1,2,10,11,14,15,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Matziolis et al [7] found a comparable drop in hemoglobin between study groups. Yang et al [14] failed to differentiate between tourniquet use and no tourniquet use.…”
mentioning
confidence: 72%
“…In the Introduction, the authors compared randomized controlled trials featuring patients undergoing TKA with or without tourniquet that show no statistical difference in blood loss or less blood loss when no tourniquet is used. The authors provided three additional studies [2,6,13] in their References section. However, none of these three papers have studied blood loss with or without tourniquet in TKA.…”
mentioning
confidence: 99%